2021
DOI: 10.1245/s10434-021-09747-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Time from Diagnosis to Breast-Conserving Surgery is Associated with Upstaging in Hormone Receptor-Positive Invasive Ductal Breast Carcinoma

Abstract: Background Time to surgery (TTS) has been suggested to have an association with mortality in early-stage breast cancer. Objective This study aims to determine the association between TTS and preoperative disease progression in tumor size or nodal status among women diagnosed with clinical T1N0M0 ductal breast cancer. Methods Women diagnosed with clinical T1N0M0 ductal breast cancer who had breast-conserving surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This cohort study showed that delay in surgery is associated with disease progression among estrogen receptor (ER)-positive T1N0M0 ductal breast cancer patients who received breast-conserving surgery as their first definitive treatment; however, no such association was observed in ER-negative patients. 5 This study concluded that avoiding an excessive delay of surgery may reduce preoperative disease progression.…”
Section: Presentmentioning
confidence: 90%
“…This cohort study showed that delay in surgery is associated with disease progression among estrogen receptor (ER)-positive T1N0M0 ductal breast cancer patients who received breast-conserving surgery as their first definitive treatment; however, no such association was observed in ER-negative patients. 5 This study concluded that avoiding an excessive delay of surgery may reduce preoperative disease progression.…”
Section: Presentmentioning
confidence: 90%
“…Furthermore, staging, histopathologic grading, tumor size, molecular subtype, and genomic testing results, unavailable in claims data, have predictive value for modeling time to treatment and selection of early-stage patients most likely to experience worsened survival with delay. 11 15 To address this, we excluded patients with claims that might reflect distant metastases, a method that despite having modest sensitivity (72.8%) has a greater than 94% negative predictive value. 45 Our analysis did not differentiate between types of additional encounters during the biopsy-to-surgery interval, such as imaging, diagnostic work-ups, or transfers of care, which are known to contribute to delays.…”
Section: Discussionmentioning
confidence: 99%
“… 3 6 Many contributors to the duration of the preoperative period of recently diagnosed patients are clinically appropriate and include surgical scheduling logistics requisite to case complexity, transfers of care, the seeking of second opinions, imaging, and treatment with neoadjuvant chemotherapy. 7 10 For patients with early-stage disease, however, surgical delays beyond 60 days have been associated with tumor and nodal upstaging, 11 , 12 as well as decreased survival, 4 , 12 15 with longer delays having a more pronounced adverse impact. Whereas numerous guidelines and quality measures have been established to define clinically appropriate intervals between breast cancer diagnosis and initiation of adjuvant chemotherapy, radiation, or endocrine therapy, guidelines specifying a recommended interval from diagnosis to surgery were lacking until 2020.…”
mentioning
confidence: 99%
“…Our attention is focused on the final treatment option, pharmacological therapy, which is used to minimizetumor burden and prevent, control, or treat cancer spread. Hormonal therapy, which involves hormones or hormone-like substances, is frequently used in the treatment of breast cancer [ 18 ].Recent advances in molecular biology and immunotherapy have increased the inclusion of targeted medicines suited to the unique pathophysiology of several breast cancer subtypes. This technique often includes the use of a small chemical or monoclonal antibody to target a particular molecular pathway ( Figure 1 and Table 2 ), therefore preventing or controlling cancer proliferation, progression, dissemination, and/or treatment resistance.Trastuzumab (herceptin) is the most well-known targeted treatmentup to date.…”
Section: Introductionmentioning
confidence: 99%
“…This technique often includes the use of a small chemical or monoclonal antibody to target a particular molecular pathway ( Figure 1 and Table 2 ), therefore preventing or controlling cancer proliferation, progression, dissemination, and/or treatment resistance.Trastuzumab (herceptin) is the most well-known targeted treatmentup to date. It is a humanized anti-HER2 monoclonal antibody [ 18 ]. At the moment, adjuvant therapy treatment is mostly determined by the intrinsic subtype of breast cancer.…”
Section: Introductionmentioning
confidence: 99%